Understanding GBS infection in pregnancy: exploring adverse maternal and pregnancy outcomes and the prospect of a GBS vaccine - Monica Sosa; Linda O. Eckert; Alisa Kachikis (Therapeutic Advances in Infectious Disease)
Group B streptococcus (GBS) or Streptococcus agalactiae is a beta-hemolytic, Gram-positive coccus that can colonize the genitourinary and gastrointestinal tract of pregnant people. GBS can transition from asymptomatic colonization to pathogenic bacterium which can then lead to adverse pregnancy, maternal and neonatal outcomes. While much of the literature focuses on outcomes affecting the neonate, such as early- and late-onset neonatal sepsis, GBS is also thought to be associated with specific pregnancy and fetal adverse outcomes including preterm birth, preterm premature rupture of membranes, urinary tract infection, endometritis, and maternal sepsis. The objective of this literature review is to further address the known associations of these maternal and pregnancy outcomes, review the current strategies for GBS screening and preventative strategies, and explore the current maternal GBS vaccine candidates in development that may address the limitations of current prevention strategies with intrapartum antibiotic prophylaxis.